2011
DOI: 10.1590/s0074-02762011000400005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined polymorphisms in chemokines and chemokine receptors on the clinical course of HIV-1 infection in a Brazilian population

Abstract: Polymorphisms in genes that encode chemokines or their receptors can modulate susceptibility to human immunodeficiency virus (HIV) infection and disease progression. The objective of this study was to assess the frequency of polymorphisms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…In other populations such as Brazilian, Hungarian, Chinese, Polish, and Indian, the distribution of this variant ranges between 14% and 40%. [23][24][25][26][27][28] Thus, distribution of this variant in the Jordanian population is within the range described in other countries.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In other populations such as Brazilian, Hungarian, Chinese, Polish, and Indian, the distribution of this variant ranges between 14% and 40%. [23][24][25][26][27][28] Thus, distribution of this variant in the Jordanian population is within the range described in other countries.…”
mentioning
confidence: 87%
“…29,30 On the other hand, lack of association with this polymorphism has been reported in Polish and Spanish populations. 31,32 Similarly, an association between the CCR2-64I polymorphism and progression to AIDS has been shown in Brazilian and Chinese populations 23,33 but not in Georgian and Kenyan populations. 34,35 For SDF1-3¢A, controversial associations with this polymorphism hves been reported.…”
mentioning
confidence: 98%
“…, 0.6% in Cepem, 0.7% in African-Brazilian populations from Pará (Carvalhaes et al , 2004), 0.9 and 1.0% in Bahia (Carvalho et al , 2004), 1.8% in Candelária and Bate-Estaca and 1.9% and 2.0% in African-Brazilian individuals in Rio de Janeiro (Chies and Hutz, 2003) and Paraná (Boldt et al , 2009), respectively. Among HIV + subjects, frequencies ranged from 2.1% in Rio de Janeiro (Teixeira et al , 2009) to 2.4% in Rio Grande do Sul (Vieira et al , 2011), 2.6% in a miscegenated population in Bahia (Grimaldi et al , 2002) and 3.8% in São Paulo (Rigato et al , 2008). Hünemeier et al (2005) found frequencies of 2.0 and 3.0% in Amerindian populations from south Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated a relation between CCR2V64Il, a variant of CCR2, and some inflammatory and autoimmune diseases such as coronary artery disease, diabetes mellitus, progression of HIV, chronic renal failure, and trigeminal neuralgia [8, 11, 27, 28]. These studies showed that CCR2 polymorphism plays a role in CAD and myocardial infarction pathogenesis by vessels inflammation and produced atherosclerotic plaque [8, 29].…”
Section: Discussionmentioning
confidence: 99%